Ship construction - Eyres, David J. (Butterworth-Heinemann, 2007)
Intended for students of naval architecture, ship building and construction, and for professional Naval Architects and Marine Engineers. Beginning with an introduction to ship building and concluding with the finished product, the book enables the reader to follow the construction of a ship from start to finish.